“Learning alone-a with Corona”: two challenges and four principles of tertiary teaching - Susan Rachel Banki (Journal of Research in Innovative Teaching & Learning, 2021)
Purpose – The author offers two challenges and four principles to teaching in the tertiary sector during this pandemic. While others may focus on the challenge of technical delivery, the author notes the challenges of systemic student disengagement. The author attempts to correct for this in four ways. She argues that the challenges she identifies and the principles that can be deployed in response are applicable across a range of teaching contexts and can be adapted for a post-COVID-19 era. Design/methodology/approach – This paper draws on the author's phenomenological experience teaching in the context of COVID-19 and draws as well on the sociological literature of higher education teaching. Findings – Four principles emerged from a year of successful teaching during COVID-19. First, the author embraces a pedagogy of care, which reflects a genuine concern for student well-being. Second, the author utilizes a variety of technological approaches to keep students engaged. Third, she retains a flexible approach to teaching. Fourth, she considers carefully the extent to which COVID-19 is included, and excluded, from topical discussions. On this point she argues that COVID-19 should neither be the center point of any material, nor should it be ignored completely. Originality/value – Shocks to the tertiary education system will continue to recur, as will instances of systemic student disengagement. Effective correctives to such disengagement, drawn from both education theory and empirical experience, will continue to be of value.